Retinal regeneration is facilitated by the presence of surviving neurons. Issue 9 (18th February 2014) - Sherpa, Tshering; Lankford, Tyler; McGinn, Tim E.; Hunter, Samuel S.; Frey, Ruth A.; Sun, Chi; Ryan, Mariel; Robison, Barrie D.; Stenkamp, Deborah L.
ABSTRACT Teleost fish regenerate their retinas after damage, in contrast to mammals. In zebrafish subjected to an extensive ouabain‐induced lesion that destroys all neurons and spares Müller glia, functional recovery and restoration of normal optic nerve head (ONH) diameter take place at 100 days postinjury. Subsequently, regenerated retinas overproduce cells in the retinal ganglion cell (RGC) layer, and the ONH becomes enlarged. Here, we test the hypothesis that a selective injury, which spares photoreceptors and Müller glia, results in faster functional recovery and fewer long‐term histological abnormalities. Following this selective retinal damage, recovery of visual function required 60 days, consistent with this hypothesis. In contrast to extensively damaged retinas, selectively damaged retinas showed fewer histological errors and did not overproduce neurons. Extensively damaged retinas had RGC axons that were delayed in pathfinding to the ONH, and showed misrouted axons within the ONH, suggesting that delayed functional recovery following an extensive lesion is related to defects in RGC axons exiting the eye and/or reaching their central targets. The atoh7, fgf8a, Sonic hedgehog (shha), and netrin‐1 genes were differentially expressed, and the distribution of hedgehog protein was disrupted after extensive damage as compared with selective damage. Confirming a role for Shh signaling in supporting rapid regeneration, shhat4+/‐ zebrafish showed delayed functional recovery after selective damage. We suggest that surviving retinal neurons provide structural/molecular information to regenerating neurons, and that this patterning mechanism regulates factors such as Shh. These factors in turn control neuronal number, retinal lamination, and RGC axon pathfinding during retinal regeneration. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 74: 851–876, 2014